Hope and mental health problems among orphans and vulnerable children in South Africa. Issue 2 (1st February 2023) - Allman, Madeleine; Penner, Francesca; Hernandez Ortiz, Jessica; Marais, Lochner; Rani, Kholisa; Lenka, Molefi; Cloete, Jan; Sharp, Carla
ABSTRACT : There are over three million orphaned and vulnerable children (OVC) currently living in South Africa. OVC are at high risk for a number of negative outcomes, including poor mental health. Hope has been associated with well-being among youth, including youth in South Africa. However, the relationships between hope and mental health in high-adversity populations such as OVC has not been adequately described. The present study sought to address this research gap by evaluating the relationship between hope and mental health, controlling for gender, age, and orphan status, among OVC. This study includes 8- to 12-year-old OVC (N = 61) in Manguang, Free State, South Africa. Hope was assessed using the Children's Hope Scale (CHS) and mental health outcomes were assessed using the Strengths and Difficulties Questionnaire (SDQ). Hope was significantly, inversely associated with mental health outcomes after controlling for other variables in linear regression analysis. In contrast to previous research, this study found that increased hope scores were associated with adverse mental health outcomes among OVC in South Africa. Hope may be contextualized differently in this population due to resource scarcity and high rates of adversity including HIV-AIDS related stigma and poverty.